Smart Parking Sensors, Technologies and Application Based IoT - GR, Prakruthi; biradar, Arun (International Journal of Computer Sciences and Engineering, 2025)
the major problem in day to day life is parking of vehicles especially the car parking at an particular place. And this issue indirectly leads to traffic congestion. A basic concept of using IoT insmart parking services in the smart cities as an important application of the Internet of Things (IoT). the system can will be accessible through a mobile app or through the webpage and it can be used to monitor then to find the empty slots in that area. the user can be parking their vehicle in the empty slot through the mobile application and before only he can book his slot for the particular time in particular place.